STUDENTS’ USE OF MULTIPLE INTELLIGENCE IN EFL CLASSROOM AT VOCATIONAL HIGH SCHOOL MAKASSAR OF SOUTH SULAWESI - Ridayani Ridayani; Awaludin Rizal (Jurnal Bilingual, 2022)
This study aimed at finding out the types of multiple intelligence used by students at the tenth grade of SMK Bina Insani Makassar, and which type was dominantly used by students. The objectives of the research were to find out (1) the types of multiple intelligence used by students, (2) the dominant type of multiple intelligence used by students. The researchers applied descriptive quantitative research to analyze of data. The subject of the research was the tenth grade of students at SMK Bina Insani Makassar consisting of 30 students and selected by using random sampling technique. The research used the Multiple Intelligence Inventory which was adapted from Walter McKenzie’s Inventory as the instrument. The research covered eight of multiple intelligence namely: Verbal-Linguistic Intelligence, Logical-Mathematical Intelligence, Visual-Spatial Intelligence, Bodily-Kinesthetic Intelligence, Musical Intelligence, Interpersonal Intelligence, Intrapersonal Intelligence, Naturalistic Intelligence. The research showed that the type of multiple intelligence that were used by students in high category namely Intrapersonal Intelligence 26 (86.7%). The type of multiple intelligence that were used by students in moderate category namely Logical-Mathematical Intelligence 20 (66.7%). The type of multiple intelligence that were used by students in low category namely Interpersonal Intelligence 8 (26.6%). Then the dominant type of multiple intelligence based on highest score was Intrapersonal Intelligence with the score 247. The result of the findings indicated that most of students at the tenth grade used Intrapersonal Intelligence.